La falta de especialidad de jueces de primer nivel para tratar casos constitucionales, en la ciudad de Machala, provincia de El Oro 2013 - 2014. - Moreno Cruz, Mirian Jeannette (2015)
The Ecuadorian State adopted the neo constitutionalism as state ideology . This implies a strengthening of constitutional justice specialist , giving birth to the Constitutional Court , charged primarily abstract and interpretation of the constitutional control.